Ultra-low-Cycle Fatigue Failure of Metal Structures under Strong Earthquakes - Jia, Liang-Jiu.; Ge, Hanbin; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents experimental results and theoretical advances in the field of ultra-low-cycle fatigue failure of metal structures under strong earthquakes, where the dominant failure mechanism is ductile fracture. Studies on ultra-low-cycle fatigue failure of metal materials and structures have caught the interest of engineers and researchers from various disciplines, such as material, civil and mechanical engineering. Pursuing a holistic approach, the book establishes a fundamental framework for this topic, while also highlighting the importance of theoretical analysis and experimental results in the fracture evaluation of metal structures under seismic loading. Accordingly, it offers a valuable resource for undergraduate and graduate students interested in ultra-low-cycle fatigue, researchers investigating steel and aluminum structures, and structural engineers working on applications related to cyclic large plastic loading conditions.
Foreword by Prof. Yiyi Chen -- Foreword by Prof. Hitoshi Kuwamura -- Preface -- Steel and aluminum -- Fracture of metal structures in past strong earthquakes -- Metal plasticity under monotonic loading till fracture -- Cyclic metal plasticity at extremely large plastic strain -- Ductile fracture of steel under monotonic loading -- Ultra-low-cycle fatigue of steel -- Ultra-low-cycle fatigue failure of aluminum -- Applications to metal structures -- Appendix: Integration algorithm for modified Yoshida-Uemori model.
Keywords: Mechanics, Applied; Solids; Building materials; Buildings -- Design and construction; Fire prevention; Buildings -- Protection; Geotechnical engineering; Solid Mechanics; Building Materials; Building Construction and Design; Fire Science, Hazard Control, Building Safety; Geotechnical Engineering and Applied Earth Sciences